ANALISIS FIQH SIYASAH PERAN TOKOH MASYARAKAT DALAM PROSES PEMEKARAN DESA: (Studi di Desa Darubiah Kec. Bonto Bahari Kab. Bulukumba) - Rappe, Ambo; Ishak, Nurfaika (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
This study aims to determine how the role of community leaders in village expansion in Darubiah Village, Kec. Bonto Bahari Kab. Bulukumba? What are the factors that influence the role of community leaders in the expansion of Darubiah village, Kec. Bonto Bahari Kab. Bulukumba? What is the view of siyasa fiqh about the role of community leaders? The main problem of this research is how to analyze the fiqh siyasah of the role of community leaders in the process of expanding the study village in Darubiah Village, Kec. Bonto Bahari Kab. Bulukumba. The type of research used is field qualitative, using a syar'i normative approach and a sociological approach. The results of this study indicate that,The role of community leaders in the process of village expansion has a role as a motivator, dynamist, who is able to provide moral encouragement, advice, advice, to carry out guidance so that community members participate in participating in village expansion in Darubiah Village, The factors that most influence the expansion of villages in Darubiah Village, Bonto Bahari District, Bulukumba Regency are geographical factors, administrative factors, political factors, development equity factors, economic factors, juridical factors, socio-cultural factors, and historical factors, In the Fiqh Siyasah perspective, so far community leaders have played a role and carried out their duties in village expansion according to Islamic law.